2016
DOI: 10.3390/math4040057
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dynamics in Multiphysics Modelling of Active Faults

Abstract: Instabilities in Geomechanics appear on multiple scales involving multiple physical processes. They appear often as planar features of localised deformation (faults), which can be relatively stable creep or display rich dynamics, sometimes culminating in earthquakes. To study those features, we propose a fundamental physics-based approach that overcomes the current limitations of statistical rule-based methods and allows a physical understanding of the nucleation and temporal evolution of such faults. In parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…using Gr as the continuation parameter) for various values of Le, as well as some continuation analyses along Le for various values of Gr. Figure 1A shows that both series lead to the determination of the same boundary for the zone of oscillations and contribute to refine the original picture shown on Figure 1B, originally obtained (Alevizos, et al, 2016) with a limited series of continuations for = 0.6, 0.7, 0.8, 0.9, 1.0.…”
Section: Methods and Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…using Gr as the continuation parameter) for various values of Le, as well as some continuation analyses along Le for various values of Gr. Figure 1A shows that both series lead to the determination of the same boundary for the zone of oscillations and contribute to refine the original picture shown on Figure 1B, originally obtained (Alevizos, et al, 2016) with a limited series of continuations for = 0.6, 0.7, 0.8, 0.9, 1.0.…”
Section: Methods and Resultsmentioning
confidence: 91%
“…A stability analysis with respect to Gr showed a steady-state response of the system in the shape of an "S-curve", with a lower branch representing the steady-state response of the fault creeping at geological strain rate, and an upper branch characterising fast slip events, either in the form one continuous slip or as episodic stick-slip events. A further study (Alevizos, et al, 2016) showed the importance of Le, whose values affect strongly the shape and stability regime of the S-curve. In particular, that work showed the existence of a critical value Lec below which oscillations can't exist, regardless of the value of Gr.…”
Section: Physical Modelmentioning
confidence: 99%
See 1 more Smart Citation